MAKNA KEBERSAMAAN SEBAGAI NILAI KONSELING ISLAM DALAM MEMBACA DZIKIR ROTIBUL HADDAD - Dasuki; Wawan Juandi (Fakultas Dakwah Universitas Ibrahimy, 2022)
The meaning of togetherness is to establish intimacy in reading dhikr reading rotibul haddad. In this case we can maintain togetherness within the scope of the Islamic Boarding School. From the research conducted to examine the togetherness carried out in the Pondok Pesantren environment in the reading of dhikr rotibul haddad, namely, using Islamic counseling togetherness which we often hear is only limited to relatives or closest relatives. However, it is necessary that we together find things that can be re-examined, such as the togetherness carried out by the students in the reading of the rotibul haddad dhikr. The aim of this research is to develop more from various perspectives. The method used in the research conducted by the researcher is using the exploratory study method. From the results of field observations, it is found what if it is worth studying. From the perspective of Islamic Counseling in the Meaning of Togetherness in Reading Rotibul Haddad, one of which is to cultivate the nature of caring for others and being able to establish intimacy or mutual need between one another. The conclusion from the results of the research conducted is to cultivate habits towards others in the Pondok Pesantren environment and also to be able to establish comfort. Against each other to maintain the togetherness.